The Geometric Redesign of Horizontal Curved Using AutoCAD Civil 3D®: A Case Jalan Garuda – Jalan Moh. Hatta, Tasikmalaya West Java - Nida Ulchurriyyah; Andri Irfan Rifai; Mohamad Taufik (Indonesian Journal of Multidisciplinary Science, 2022)
Highways are needed because they are the most widely used transportation infrastructure to support the economy and daily human activities that function to pass traffic on it quickly, safely, and comfortably. In today's world of rapid digital improvement, road planning using AutoCAD Civil 3D® results in a more efficient, accurate, and time-saving road planning process than road planning using manual methods. The horizontal alignment of the road determines the location of the road in question. The horizontal alignment has three geometric components: tangent, curve, and transition between straight line and arch. The purpose of writing this paper is to plan the geometric road on the North Ring Road section Jalan Garuda - Jalan Moh. Hatta in the northern area of Tasikmalaya, West Java. The road is planned to add land transportation facilities and connect the Cibeureum District - Cipedes District. The length of the road section is 1016 m or 1,016 km (STA 0+000 – STA 1+016.79).